Emergence of ST11-KL64 carbapenem-resistant hypervirulent Klebsiella Pneumoniae isolates harboring bla KPC−2 and iucA from a tertiary teaching hospital in Western China - Haojun Chen; Tingting Li; Xiaoxue Huang; Qiurong He (BMC Infectious Diseases)
Abstract Background Carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-HvKP) poses a critical global health threat. However, molecular epidemiological data on CR-HvKP in Western China remain scarce. This study aimed to characterize the clinical profiles, molecular features, and risk factors of CR-HvKP isolates in Western China. Methods Sixty-eight carbapenem-resistant Klebsiella pneumoniae (CRKP) clinical isolates were collected from January to December in 2024. Clinical characterization included antimicrobial susceptibility profiling and hypermucoviscosity assessment via string test. Detection of carbapenemases using inhibitor enhancement test. Molecular characteristics of CRKP included serotype, carbapenemases, virulence-associated factors, and multilocus sequence typing (MLST) performed by using the PCR method. CR-HvKP was defined as the presence of any one of rmpA, rmpA2, iroB, iucA, and peg-344. Risk factors were initially evaluated using univariate logistic regression analysis, with significant variables subsequently incorporated into a multivariate regression model. A p-value < 0.05 was considered statistically significant. Results Among 68 CRKP isolates, 36 were identified as CR-HvKP, all harboring the iucA gene (100%, 36/36). However, only 22.2% (8/36) of string test results correlated with virulence gene presence. All CRKP strains exhibited high resistance to most antibiotics, with comparatively lower resistance rates observed for tigecycline (0%) and polymyxin B (14.7%). Carbapenemase production was the predominant resistance mechanism, with 61.8% (42/68) carrying bla KPC−2. Serotyping and MLST revealed that ST11-KL64 CR-HvKP being predominant. A novel wzi752 allele was identified, encoding amino acid sequences homologous to serotype KL47. Univariate analysis demonstrated significantly higher ICU admission rates (p = 0.018) and carbapenem exposure (p = 0.023) in CR-HvKP patients with infections. Multivariate analysis highlighted borderline significance for ICU admission (OR = 2.939, p = 0.056) as a potential risk factor. Conclusions The ST11-KL64 CR-HvKP clone harboring bla KPC−2 and iucA has emerged as a dominant pathogen of hospital infections in Western China, posing dual threats of resistance and virulence. Enhanced molecular surveillance and infection control strategies are urgently needed to mitigate its spread.